The Measurement of Supply Chain Management Performance at PT. Sinergi Gula Nusantara Sei Semayang Sugar Factory Unit in 2020 – 2023 Using The Supply Chain Operation Reference-Fuzzy Analytical Hierarchy Process (SCOR-FAHP) Method - Audina Afriani; Pratami Wulan Tresna; Luthfi Thirafi (Dinasti Publisher, 2024)
PT. Sinergi Gula Nusantara Sei Semayang Sugar Factory unit is a sugar-producing company which collaborates with suppliers and distributors along its supply chain. The challenges which are faced by PT. Sinergi Gula Nusantara Sei Semayang Sugar Factory unit, are delays in raw material deliveries and production schedules, limitations and mismatches of raw materials with criteria, and production outcomes not meeting targets. Therefore, it is necessary to measure supply chain management performance in order to know the conditions and assess the performance of supply chain management at PT. Sinergi Gula Nusantara Sei Semayang Sugar Factory unit, from 2020 to 2023. Furthermore, the methods used were SCOR as the model for mapping the measurement matrix and FAHP was used in order to determine the priority weights for each criterion in the matrix. The supply chain management performance measurement results at PT. Sinergi Gula Nusantara Sei Semayang Sugar Factory unit, from 2020 to 2023, obtain a score of 81.24, which is categorized into good category. However, there are still 5 KPIs which need improvement, in which it can be achieved by improving record-keeping and documentation with software assistance, sorting raw materials, and implementing the SCOR-FAHP method in supply chain management performance measurement.